Impacts of problem-based learning towards calculus achievement and mathematical critical thinking skills among pre–university students - Ramli, M. S.; Ayub, A. F. M.; Razali, F.; Ghazali, N.; Norudin, S. W. A. W. (Universiti Putra Malaysia, 2024)
Pre-university students often struggle with calculus, particularly integration, and critical thinking skills, which are vital for industry needs. This study investigates the impact of problembased learning (PBL) on calculus achievement and mathematical critical thinking skills among pre-university students. Using a control group and a quasi-experimental design, the research involved 48 pre-university college students. Participants were divided into two groups: 24 students received PBL instruction, while 24 students followed a conventional approach. Students’ achievement in calculus and mathematical critical thinking skillswas assessed through pre-tests, post-tests, and delayed post-tests. The analysis revealed a significant improvement in calculus achievement and mathematical critical thinking skills among students who experienced PBL compared to those who received conventional instruction. The findings suggest that PBL is more effective than conventional teaching methods, and its continued use in future educational settings is recommended.